Gen Z's Personal Data Protection Literacy Towards a Healthy Digital Culture - Retno Kusniati; Andi Najemi; Andi Agus Salim (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2026)
The exponential advancement of information and communication technology over the preceding decade has catalyzed profound digital transformation across diverse societal strata, encompassing traditional religious educational institutions such as Islamic boarding schools (pondok pesantren), which are now largely comprised of Generation Z students (santri). However, this rapid digitalization is frequently decoupled from a commensurate level of legal literacy, specifically regarding the intricacies of personal data protection and the ethical imperatives of interaction within cyberspace. Such a lack of juristic comprehension engenders various legal vulnerabilities for santri, including unauthorized information dissemination (doxing), cyber-victimization (cyberbullying), and the potential for identity data manipulation by malicious actors. Consequently, Pondok Pesantren Al Jauharen in Jambi was designated as a strategic collaborative partner, predicated on the current absence of a systematic framework for developing digital legal consciousness among its students. This community engagement initiative is designed to equip santri with an exhaustive legal understanding of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) as part of a collective effort to institutionalize a healthy, ethical, and accountable digital culture. The methodological framework was implemented via a participatory approach involving interactive case-based legal discourse, creative digital content production workshops, and empirical evaluation through pre-test and post-test instrumentation. The outcomes demonstrated a significant elevation in the participants' awareness regarding the sanctity of personal data protection, thereby fulfilling the pedagogical and juristic objectives established by the program facilitators.